2017
DOI: 10.1371/journal.pone.0176404
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative microvascular analysis of retinal venous occlusions by spectral domain optical coherence tomography angiography

Abstract: PurposeTo quantitatively evaluate the retinal microvasculature in human subjects with retinal venous occlusions (RVO) using optical coherence tomography angiography (OCTA).DesignRetrospective, cross-sectional, observational case series.ParticipantsSixty subjects (84 eyes) were included (20 BRVO, 14 CRVO, 24 unaffected fellow eyes, and 26 controls).MethodsOCTA was performed on a prototype, spectral domain-OCTA system in the 3x3mm central macular region. Custom software was used to quantify morphology and densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 22 publications
4
79
2
1
Order By: Relevance
“…In eyes with BRVO, decrease in VD and VL are also reported in 3 × 3 mm scan area which is much more limited compared with current study (Koulisis et al. ). As we stated, few reports have assessed the efficacy of wide‐field OCTA so that VL can be the marker of development on retinal nonperfusion in BRVO.…”
Section: Discussioncontrasting
confidence: 81%
“…In eyes with BRVO, decrease in VD and VL are also reported in 3 × 3 mm scan area which is much more limited compared with current study (Koulisis et al. ). As we stated, few reports have assessed the efficacy of wide‐field OCTA so that VL can be the marker of development on retinal nonperfusion in BRVO.…”
Section: Discussioncontrasting
confidence: 81%
“…Existing studies have reported enlarged foveal avascular zone (FAZ) area in retinal ischaemic diseases such as diabetic retinopathy (DR)10 and retinal vascular obstruction (RVO)11; decreased FAZ area in retinopathy of prematurity12; decreased vessel density in DR10 and glaucoma13; lower fractal dimension in RVO,11 DR10 and uveitis eyes14; increased vessel diameter index (VDI) in RVO11 and DR10; and decreased FAZ circularity in glaucoma15 and DR 10. These studies demonstrate that quantitative OCTA metrics may provide useful information for the diagnosis of ocular diseases potentially.…”
Section: Introductionmentioning
confidence: 99%
“…Multivariable linear regressions were used to compare the 3Dmeasures across groups. The generalized estimating equation (GEE) method was used to control for age, gender, and between-eye correlation when appropriate [6]. All statistical analysis was considered significant for p-value set to 0.05.…”
Section: ) Quantitative Resultsmentioning
confidence: 99%
“…Optical Coherence Tomography Angiography (OCTA) is a novel and non-invasive modality that is clinically approved to evaluate the retinal vasculature [1][2][3]. It has been applied in studying various ophthalmological diseases such as age-related macular degeneration (AMD), diabetic retinopathy (DR), uveitis, vein occlusions, and glaucoma [4][5][6][7][8][9]. In addition, OCTA has been shown to be a valuable imaging modality to identify changes in the microvascular network caused by neurovascular diseases [10][11][12][13].…”
Section: Index Terms-optical Coherence Tomography Angiography 3d Vesmentioning
confidence: 99%